2010
DOI: 10.1590/s1519-38292010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento do olhar e do contato ocular em lactentes de zero a quatro meses de idade

Abstract: OBJETIVOS: investigar o desenvolvimento do contato ocular e do comportamento visual de bebês entre zero e quatro meses. MÉTODOS: dezessete bebês típicos foram filmados mensalmente por 30 minutos, sendo transcritas 11 categorias de observação do olhar, quantificadas e tratadas estatisticamente através dos testes de Friedman (α = 0,050) e dos Postos Sinalizados de Wilcoxon (α de Bonferroni = 0,010). RESULTADOS: houve diferenças estatisticamente significantes nas frequências das categorias: "olhar para os olhos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…In this sense, it is fundamental to consider that the adult of the dyad was the mother, who knows the communicative needs of her child. The mother is the facilitator in this process and during the data gathering moments places the child as the central focus of her attention (1,2,7,8,14) . Prior studies suggest that the child learns to use language, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this sense, it is fundamental to consider that the adult of the dyad was the mother, who knows the communicative needs of her child. The mother is the facilitator in this process and during the data gathering moments places the child as the central focus of her attention (1,2,7,8,14) . Prior studies suggest that the child learns to use language, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The data has shown that the babies seek communication's interactivity since the first days of life. Prior studies with older children (13) and babies (1) concluded that the larger part of children's communicative acts have interpersonal functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations